Gender consciousness through applied theatre - Sales Oliveira, C. (2019)
This paper describes an experience of the use of applied theatre for the promotion of gender equality. The fact that women continue to face multiple forms of discrimination as human beings, citizens and professionals justified the search of alternative training models. The Empowerment Labs focused on the amplification of power, freedom and action of two groups of women: university students and unemployed women. The core of the approach followed was guided by a fundamental question: ‘can theatre raise consciousness and empowerment in the context of gender equality?’ The results obtained through different internal assessment tools provide evidence of change in what feminist awareness and personal empowerment are concerned. We present and discuss the process and results of this experience including the advantages and limitations of applied theatre in certain types of outcomes.